The under 40 financial planning guide : from graduation to your first house - McCarthy, Cornelius P. (Merritt Pub., 1996)
The author, an investment banker and attorney, explains money management for people, like him, who are under forty. Includes chapters on budgets, needs, taxes, credit and debt, buying a car, insurance, investments, wills, and buying a house.